The barracks of the Roman Army from the 1st to 3rd centuries A.D. : a comparative study of the barracks from fortresses, forts, and fortlets with an analysis of building types and construction, stabling, and garrisons - Davison, David P. (Archaeopress Archaeology, 1989)
This study offers a comparative study of the barracks from Roman fortresses, forts and fortlets with an analysis of building types and construction, stabling, and garrisons, seeking to address many direct questions where there is lack of useful written evidence.